Moderate Islam: The Religious Foundation of the Muhammadiyah Movement in Indonesia - Ritonga, Raja; Dahlan, Dasrizal; Lahmi, Ahmad; Asmaret, Desi; Ritonga, Ahmad Roisuddin; Elhusein, Shofwan Karim (PERADA, 2024)
Islam as a doctrine capable of addressing every aspect of the community’s issues, will continue to evolve with the times. Muslims are expected to be critical and to have a moderate conceptual framework in interpreting religious texts. This approach will inevitably influence individual movements and religious practices. Muhammadiyah, as one of the largest social organizations in Indonesia, has a deeply rooted religious movement that extends down to the grassroots. This article discusses the concept of moderation as a religious foundation that underpins the Muhammadiyah Islamic Movement in Indonesia. The research method employed is a literature review of the thoughts and teachings embraced by the Muhammadiyah Movement. From this analysis, the article concludes that the religious foundation of the Muhammadiyah Movement includes moderate Islamic principles, an emphasis on education, inclusive da’wah, and social services. This conclusion provides a deeper understanding of the role of the Muhammadiyah Movement in shaping religious identity and its contributions to community development in Indonesia.